Presentation and Outcomes of Childhood Cancer Patients at Uganda Cancer Institute. (May 2019) - Mutyaba, Innocent; Wabinga, Henry R.; Orem, Jackson; Casper, Corey; Phipps, Warren
Introduction . Limited data suggest that children with cancer in sub-Saharan Africa have poor survival. We aimed to describe the presentation, treatment outcomes, and factors associated with survival among children with cancer managed at Uganda Cancer Institute. Methods . We retrospectively evaluated patients with childhood cancer (age ≤19 years) from Kyadondo County treated at Uganda Cancer Institute from 2006 to 2009. Cox's regression and Kaplan-Meier methods were used to study 1-year survival. Results . Among 310 patients studied, median age was 7 years (range = 0.25-19 years), 64% were boys, and 92% had histological confirmation of cancer diagnosis. The commonest diagnoses were Burkitt lymphoma (BL, N = 87), Kaposi sarcoma (KS, N = 68), non-BL non-Hodgkin lymphoma (NHL, N = 32), acute lymphoblastic leukemia (ALL, N = 28), Wilms (N = 28), and Hodgkin disease (HD, N = 20). Advanced disease at diagnosis was common for all cancers (ranging from 45% for KS to 83% for non-BL NHL). Overall, 33.2% abandoned treatment. One-year survival was 68% for HD (95% confidence interval [CI] = 11.3-40.6), 67% for KS (95% CI = 52.1-77.9), 55% for BL (95% CI = 42-66.9), 44% for Wilms (95% CI = 22.5-63), 43% for non-BL NHL (95% CI = 23.3-61.3), and 20% for ALL (95% CI = 6.4-38.7). In univariate and multivariate analysis, anemia and thrombocytopenia were associated with mortality for several cancers. Conclusion . Survival among children with cancer in Uganda is poor. Advanced stage disease and loss to follow-up likely contribute to poor outcomes. Anemia and thrombocytopenia may augment traditional staging methods to provide better prognostic factors in Uganda and warrant further evaluation.